The Christmas Sweater : A Picture Book - Schoebinger, Chris; Dorman, Brandon; Beck, Glenn; Balfe, Kevin; Wright, Jason F. (New York : Aladdin/Mercury Radio Arts, 2009)
More than anything, Eddie wants a bicycle for Christmas, but his grandfather shows him the magic there can be in a simple gift made with love.
aPicture book version of a novel of the same name first published in 2008.
Keywords: Gifts -- Fiction; Sweaters -- Fiction; Grandfathers -- Fiction; Christmas -- Fiction